Potentially inappropriate prescribing in hospitalised children: a retrospective, cross-sectional study at a tertiary children’s hospital in China - Linan Zeng; Lingli Zhang; Dan Yu; Huiqing Wang; Liang Huang; Siyu Li; Guo Cheng; Zhi-Jun Jia (BMJ Open)
Introduction For improving and optimising drug use in children, we previously developed a tool (including a series of criteria for identifying potentially inappropriate prescribing in children) by literature review and the two-round Delphi technique to prevent inappropriate medication prescriptions at the prescribing stage.Objective To assess the prevalence of potentially inappropriate prescription (PIP) among hospitalised children and explore risk factors associated with PIP.Design A retrospective cross-sectional study.Setting A tertiary children’s hospital in China.Participants Hospitalised children with complete medical records who received drug treatment and discharged from 1 January to 31 December 2021.Outcome measures We evaluated the medication prescriptions by using a series of previously developed criteria for detecting the prevalence of PIP in hospitalised children and used logistic regression to explore the risk factors (including sex, age, number of drugs, number of comorbidities, days of hospitalisation and admission departments) for PIP in children.Results A total of 87 555 medication prescriptions for 16 995 hospitalised children were analysed, and 19 722 PIPs were detected. The prevalence of PIP was 22.53%, and 36.92% of the children had at least one PIP during hospitalisation. The department with the highest prevalence of PIP was the surgical department (OR 9.413; 95% CI 5.521 to 16.046), followed by the paediatric intensive care unit (PICU; OR 8.206; 95% CI 6.643 to 10.137). ‘Inhaled corticosteroids for children with respiratory infections but without chronic respiratory diseases’ was the most frequent PIP. Logistic regression results showed that PIP was more likely to occur in male patients (OR 1.128, 95% CI 1.059 to 1.202) and younger patients (<2 years old; OR 1.974; 95% CI 1.739 to 2.241), and in those with more comorbidities (≥11 types; OR 4.181; 95% CI 3.671 to 4.761), concomitant drugs (≥11 types; OR 22.250; 95% CI 14.468 to 34.223) or longer hospital stay (≥30 days; OR 8.130; 95% CI 6.727 to 9.827).Conclusions Medications for long-term hospitalised young children with multiple comorbidities should be minimised and optimised, to avoid PIP, reduce adverse drug reactions and ensure children’s medication safety. The surgery department and PICU had a high prevalence of PIP in the studied hospital and should be the focus of supervision and management in routine prescription review.